Cosmic Himalayas: The Highest Quasar Density Peak Identified in a 10,000 deg2 Sky with Spatial Discrepancies between Galaxies, Quasars, and IGM H i - Yongming Liang; Masami Ouchi; Dongsheng Sun; Nobunari Kashikawa; Zheng Cai; Sebastiano Cantalupo; Kentaro Nagamine; Hidenobu Yajima; Takanobu Kirihara; Haibin Zhang; Mingyu Li; Rhythm Shimakawa; et al. (The Astrophysical Journal)
We report the identification of a quasar overdensity in the BOSSJ0210 field, dubbed the Cosmic Himalayas, consisting of 11 quasars at z = 2.16−2.20, the densest overdensity of quasars (17 σ ) in the ∼10,000 deg ^2 of the Sloan Digital Sky Survey (SDSS). We present the spatial distributions of galaxies and quasars and a H i absorption map of the intergalactic medium (IGM). On the map of 465 galaxies selected from the MAMMOTH-Subaru survey, we find two galaxy density peaks that do not fall on the quasar overdensity but instead exist at the northwest and southeast sides, approximately 25 h ^−1 comoving Mpc (cMpc) apart from the quasar overdensity. With a spatial resolution of 15 h ^−1 cMpc in projection, we produce a three-dimensional H i tomography map by the IGM Ly α forest in the spectra of 23 SDSS/eBOSS quasars behind the quasar overdensity. Surprisingly, the quasar overdensity coincides with neither an absorption peak nor a transmission peak of IGM H i but lies near the border separating opaque and transparent volumes, with the more luminous quasars located in an environment with less IGM H i . Hence, remarkably, the overdensity region traced by the 11 quasars, albeit all in coherently active states, has no clear coincidence with peaks of galaxies or H i absorption densities. Current physical scenarios with mixtures of H i overdensities and quasar photoionization cannot fully interpret the emergence of the Cosmic Himalayas, suggesting this peculiar structure is an excellent laboratory to unveil the interplay between galaxies, quasars, and the IGM.